CROWDFUNDING AS AN INNOVATIVE BANKING SERVICE: OPPORTUNITIES AND CHALLENGES FOR COMMERCIAL BANKS IN UZBEKISTAN (World Bulletin of Social Sciences, 2026)
The rapid digital transformation of financial services has positioned crowdfunding as a promising alternative financing mechanism, particularly in emerging economies. This paper examines the potential integration of crowdfunding services into the operations of commercial banks in Uzbekistan. Drawing on international experiences from developed and developing countries, the study analyzes how commercial banks can act as intermediaries or direct providers of crowdfunding platforms. The research identifies key opportunities, including enhanced financial inclusion, new revenue streams for banks, and support for SMEs and startups. At the same time, it highlights significant challenges such as regulatory gaps, low financial literacy, and infrastructure limitations in Uzbekistan. The paper proposes a phased implementation framework and policy recommendations to facilitate the adoption of crowdfunding. Findings suggest that integrating crowdfunding can strengthen the competitiveness of Uzbek commercial banks while contributing to sustainable economic development.
Keywords: Commercial Banks; Financial Innovation; Digital Banking